Experiences of patients with traumatic brain injury and their carers during transition from in-patient rehabilitation to the community: a qualitative study. Issue 17 (14th August 2017) - Abrahamson, Vanessa; Jensen, Jan; Springett, Kate; Sakel, Mohamed
Abstract: Purpose: To explore the experiences of individuals who have had a severe traumatic brain injury (TBI) and their carers in the first month post-discharge from in-patient rehabilitation into living in the community. Method: Using a qualitative approach underpinned by critical realism, we explored the narratives of 10 patients and nine carers using semi-structured interviews approximately one month post-discharge. Thematic analysis was carried out independently by two researchers. Results: Firstly, perceptions of support were mixed but many patients and carers felt unsupported in the inpatient phase, during transitions between units and when preparing for discharge. Secondly, they struggled to accept a new reality of changed abilities, loss of roles and loss of autonomy. Thirdly, early experiences post-discharge exacerbated fears for the future. Conclusions: Most patients and carers struggled to identify a cohesive plan that supported their transition to living in the community. Access to services required much persistence on the part of carers and tended to be short-term, and therefore did not meet their long-term needs. We propose the need for a case manager to be involved at an early stage of their rehabilitation and act as a key point for information and access to on-going rehabilitation and other support services. Implications for Rehabilitation: Traumatic Brain Injury (TBI) is a major cause of long-term disability. It can affect all areas of daily life and significantly reduce quality of life for both patient and carer. Professionals appear to underestimate the change in abilities and impact on daily life once patients return home. Community services maintain a short-term focus, whereas patients and carers want to look further ahead – this dissonance adds to anxiety. The study's findings on service fragmentation indicate an urgent need for better integration within health services and across health, social care and voluntary sectors. A link person/case manager who oversees the patient journey from admission onwards would help improve integrated care and ensure the patient, and carer, are at the center of service provision.